Novel Eu-containing titania composites derived from a new Eu(iii)-doped polyoxotitanate cage. Issue 1 (21st December 2015) - Lv, Yaokang; Cai, Zhiwei; Yan, Dongpeng; Su, Chang; Li, Weijun; Chen, Wei; Ren, Zhuochao; Wei, Yongge; Mi, Ouyang; Zhang, Cheng; Wright, Dominic S.
Abstract : The new cage [Ti2 O(OEt)8 (EtOH)EuCl]2 (1 ) can be used as a single-source precursor to nano-structured Eu(iii )-containing titania composites, nanoporous composites and flexible films, which are attractive fluorescent materials. Abstract : A new Eu(iii )-doped polyoxotitanate (POT) cage [Ti2 O(OEt)8 (EtOH)EuCl]2 can be used as a single-source precursor for the formation of nanostructured Eu-containing titania composites and flexible fluorescent films, which exhibit significant red luminescence and are attractive fluorescent materials.